Exploring the effects of FTAs on Chilean exports: Heterogeneous responses and financial constraints; Explorando los efectos de loa ALCs en las exportaciones Chilenas: Respuestas heterogéneas y restricciones financieras - Robert Alvarez; Eugenia Andreasen (Estudios de Economía, 2024)
In this paper, we examine the influence of Free Trade Agreements (FTAs) on Chilean exports during the past thirty years. Over the last three decades, Chile has entered into 31 FTAs with 65 countries, encompassing nearly 90% of global GDP. Despite this, there's a notable absence of empirical evidence regarding the extent and nature of the impact of these agreements on export volumes and product diversification. With a rich dataset encompassing bilateral trade flows at the product-level and key financial indicators, we employ a difference-in-differences approach to provide robust evidence of the positive impact of these FTAs on export levels and the variety of products exported. Our analysis also reveals variations in these effects based on the industries' initial export share and trading partners' income levels. Furthermore, we investigate how FTAs interacted with the financial development and capital control policies of trading partners, demonstrating their role in mitigating financial constraints on trade.
Keywords: F1; F13; F14; F63; 330; International trade; Free trade arrangements; Heterogeneous effects; financial frictions